Toward reducing the formation temperature of diopside via wet-chemical synthesis routes using chloride precursors. Issue 16 (November 2017) - Namvar, N.; Salahinejad, E.; Saberi, A.H.; Jafari Baghjeghaz, M.; Tayebi, L.; Vashaee, D.
Abstract: Reducing the formation temperature of single-phase multioxides is one of the classic challenges in ceramic processing, including wet-chemical synthesis routes. Toward pursuing this aim for diopside (MgCaSi2 O6 ), the merit of different sol-gel and coprecipitation processes using the related chloride precursors followed by calcination was compared from the viewpoints of crystallinity and homogeneity. In accordance to the results, the use of the sol-gel techniques, directed with/without an alkaline catalyst, gave rise to the unfavorable creation of multiphase and low-crystallinity structures. Regarding the coprecipitation methods, the one-step addition of a precipitant agent is accompanied by an indirect low-temperature formation of nano-diopside, while a direct crystallization into this phase was explored in the dropwise condition, albeit with a lower crystallinity. Thus, by employing a suitable synthesis processing, it is feasible to take control of a wide range of nanoparticulate diopside-based structures achieved after a low-temperature calcination.